Reactivation (long-term evolution) of silvia-pijao fault along the “quebrada la maizena “western flank of central cordillera, quindio- colombia. (2004)
The macro and microstructural characteristics of rocks along the lower portion of the “Quebradala Maizena”, in the influence zone of the Silvia- Pijao Fault, one of the major faults related to theRomeral Fault Zone (RFZ), allow to interpet a long history of deformation. These rocks belong tothe Quebradagrande and Arquía Complexes. Along the section, structural data and samples forthin sections analysis were obtained mostly in the western block adjacent to the main fault trace.Metamorphic rocks include amphibolites and hornblende - garnet - zoisite ± chlorite ± muscovite± graphite schists. Igneous bodies are granodiorite and highly serpentinized dunite. Sedimentaryrocks are mostly sandstones and calcareous mudstones. These sedimentary rocks exhibit faultedcontacts and lenticular geometry. Most fault rocks are brittle cataclastic rocks. They include breccias,microbreccias, gouge and foliated gouge. In some samples, plastic deformation is inferred frommicroscopic bands of reduced grain size (mostly in quartz), deformation bands and undulose patchyand sweeping extinction in quartz, and to a lesser extent in plagioclase, indicating an incipientdevelopment of mylonitic textures formed at low-grade metamorphic conditions. This suggests anolder record of localized deformation. These microstructures and other outcrop scale structures suchas thrust systems (duplexes and imbricates), strike-slip and normal faults with dip and obliquecomponents of movement, tectonic foliation, varying fault cross-cutting relationships and presenceof sedimentary slices and ultrabasic serpentinized bodies along the fault zone suggest a multi-statebrittle deformation and multiple reactivation of some of the fault zones.